2015
DOI: 10.1021/acs.jproteome.5b00104
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Proteomic Mass Spectrometry Characterization of Recombinant Human μ-Opioid Receptor Functionally Expressed in Pichia pastoris Cell Lines

Abstract: Human μ-opioid receptor (hMOR) is a class-A G-protein-coupled receptor (GPCR), a prime therapeutic target for the management of moderate and severe pain. A chimeric form of the receptor has been cocrystallized with an opioid antagonist and resolved by X-ray diffraction; however, further direct structural analysis is still required to identify the active form of the receptor to facilitate the rational design of hMOR-selective agonist and antagonists with therapeutic potential. Toward this goal and in spite of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This is possibly due to the low expression level of receptors, the difficulty in devising active membrane protein preparations, and the requirement of further analysis steps, such as protease digestion, following MS/ MS sequencing of relatively hydrophobic peptides. Indeed, Rosa et al 21 reported in 2015 that only six GPCRs had their primary protein sequences completely determined (i.e., over 80% sequence coverage) using proteomic analyses.…”
mentioning
confidence: 99%
“…This is possibly due to the low expression level of receptors, the difficulty in devising active membrane protein preparations, and the requirement of further analysis steps, such as protease digestion, following MS/ MS sequencing of relatively hydrophobic peptides. Indeed, Rosa et al 21 reported in 2015 that only six GPCRs had their primary protein sequences completely determined (i.e., over 80% sequence coverage) using proteomic analyses.…”
mentioning
confidence: 99%
“…While it has been used to study larger biomolecules, only recently has a class A GPCR been deposited and desorbed with a specific antagonist bound from a multicomponent mixture . An alternative approach involves the combination of in-solution and in-gel digestion with mass spectrometry facilitating a high degree of overall sequence coverage (>80%). There has also been work in which by judicious selection of ionization parameters (and detergent) noncovalent interactions have been retained, allowing for the identification of the folded ligand-bound P2Y 1 R-MRS2500 complex . However, these analyses provide no direct 3D structural information or affinities as yet.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…This study reports that the number of identified proteins is increased from 3313 when using trypsin alone for protein digestion to 3908 when using multiple proteases, and similarly, sequence coverage is increased from 24.5% to 43.4%. Moreover, several more recent studies also utilized multiple proteases for digestion to improve protein identification and protein sequence coverage, and to identify missing proteins. , Our previous studies , showed that using a protease other than trypsin or multiple proteases would be an alternative solution for protein digestion that could yield more unique peptides and higher sequence coverage to identify missing proteins and more detectable peptides to identify single amino acid variant (SAV) peptides.…”
Section: Introductionmentioning
confidence: 99%